Nursing diagnoses for critical patients with COVID-19 in Intensive Care Unit: literature review (Research, Society and Development, 2023)
Objective: To investigate the main nursing diagnoses related to critically ill patients with COVID-19 in an Intensive Care Unit. Methodology: Integrative review, the searches were carried out from February to November 2022 in the databases: LILACS, MEDLINE, BDENF, SciELO, BVS, Cochrane Library and Google Scholar. Forty-eight studies were selected for full reading, in which 34 were excluded because they did not correspond to the research objectives. Finally, the corpus of the review was composed of 14 articles. Results: 53 Nursing diagnoses were listed for critically ill patients with COVID-19 in THE ICU, the most prevalent evidenced in this review were: Deficit in self-care for food; Deficit in self-care for bathing; Ineffective breathing pattern; Risk of unstable blood glucose; Risk of infection; Risk of pressure injury; Impaired gas exchange and impaired spontaneous ventilation. Final Considerations: Nursing care based on the Nursing Process through the elaboration of nursing diagnoses, it favors an effective performance of nursing professionals, besides contributing to the critical analysis of the health conditions of the client.